Finland's public sector balance sheet - Maren Brede; Christian Henn (Baltic Journal of Economics, 2019)
We construct comprehensive public sector balance sheets for Finland for 2000-2016 by complementing general government statistics with data on public corporations and pensions. These static balance sheets show that Finland's public sector net worth at end 2016 was - 160 percent of GDP, after having registered considerable fluctuations previously, including due to asset holdings' sensitivity to equity valuations. We then expand the analysis to an intertemporal balance sheet by adding present value estimates of future fiscal flows. This allows performing fiscal stress tests and policy experiments. These suggest that Finland's public finances will remain sound if ongoing reform efforts to address aging pressures yield their expected savings. Under this assumption, intertemporal financial net worth (IFNW) of the public sector would exceed 50 percent of GDP - well within the 30-85 percent of GDP range derived in stress tests as the needed buffer to maintain positive IFNW in light of a severe shock.
Keywords: H00; H55; H60; H63; H68; H75; H81; 330; debt sustainability; Finland; intertemporal fiscal balances; Public sector balance sheet